Dynamical cluster approximation in disordered systems with magnetic impurities - Matsunaka, Daisuke (Animo Repository, 2004)
We present a theoretical method to study diluted magnetic semiconductors, beyond the single-site approximation, extending the dynamical cluster approximation (DCA). By the method, we can consider the nonlocal correlations due to disorder and discuss effects of the direct exchange interaction between magnetic impurities on the properties of the itinerant carriers. We apply the method to a three-dimensional cubic lattice system with random localized spins. We show that the strong antiferromagnetic superexchange interaction between nearest-neighbor sites suppresses the polarization of the carrier spins. ©2004 The Physical Society of Japan.